Funding pensions : issues and implications for financial markets. Proceedings of a conference held at Melvin Village, New Hampshire October, 1976 - Federal Reserve Bank of Boston ([Boston] : Federal Reserve Bank of Boston, 1976)
This is the 16th of a series of conferences sponsored by the Federal Reserve Bank of Boston. The objective is to publish the proceedings of the conference in order to provide a research base for future public policy decisions. The topic for this conference- the funding of pension plans, particularly public pensions - certainly satisfies all these criteria. The papers prepared for this conference raise two fundamental issues. The first is the massive change in the age structure of the population which raises serious questions as to the ability of future generations to finance public pension programs on a pay-as-you-go basis without levels of taxation. The second major issues is the impact of the underfunding of public pension plans on savings and capital formation.
rpm 18/04/2018
Loans
Keywords: Pensions; Pension funds